A Critical Review of Probation and parole system in Pakistan: Weakness and Strength - Fatima Ali; Dr. Rizwana Gul (Al-Amīr Research Journal for Islamic Studies, 2024)
This research presents a critical examination of the probation and parole systems in Pakistan, delving into their historical development, current effectiveness, and the multifaceted challenges they face. Probation and parole are integral to the criminal justice system, offering pathways for offender rehabilitation and societal reintegration, thereby alleviating the burden on overcrowded prisons. However, in Pakistan, these systems grapple with significant obstacles, including inadequate officer training, resource scarcity, and pervasive societal stigma. This study employs a mixed-methods approach, combining quantitative survey data from 100 stakeholders (probation officers, offenders, public) with qualitative insights from in-depth interviews and case studies. The quantitative findings reveal a mixed level of public awareness and understanding of probation and parole. While many acknowledge their potential for reducing recidivism and supporting rehabilitation, skepticism regarding current effectiveness in Pakistan is prevalent, citing lack of resources, insufficient training, and legal/structural barriers as major impediments. Societal stigma is also highlighted as a significant hindrance to reintegration. Qualitative data further substantiates these challenges, with stakeholders emphasizing the need for improved training, robust legal frameworks, community support programs, and public awareness campaigns. The research also includes an international comparison with systems in the US, UK, Canada, and Australia, highlighting Pakistan's areas for improvement, particularly in officer training, financial management, and technological adoption. Recommendations focus on increased funding, enhanced training, legal reforms, and initiatives to combat societal stigma, ultimately aiming to bolster the efficacy of Pakistan's probation and parole systems. Keywords: Probation and Parole, Criminal Justice System, Rehabilitation and Reintegration, Societal Stigma, Legal and Institutional Reforms.